Analysis of Factors Affecting The Intention To Use Digital Banking: A Case Study Among Generation Z and Generation Y at Bank Jago - Dini Gustianawati Sutarya; Faranita Mustikasari (Dinasti Publisher, 2025)
Digital developments in the banking sector have led to innovations such as mobile banking and fintech. Bank Jago is a technology-based bank in Indonesia. Although digital literacy is increasing, digital bank account ownership among Generations Z and Y remains low. This study uses the Technology Acceptance Model (TAM) framework to analyze the factors that influence the intention to use Bank Jago's digital services, without comparing between generations. Data was collected through an online survey using convenience sampling of 230 Generation Z and Y respondents in Indonesia, using a 1–5 Likert scale questionnaire. The results show that perceived usefulness, perceived ease of use, trust, attitude, and convenience have a positive effect on intention to use, while trust has a negative effect on attitude. These findings emphasize the importance of perceived usefulness, ease of use, trust, convenience, and attitude in encouraging the adoption of digital banking services.